Zimbabwe’s operation murambatsvina (operation clean up/restore order): the epitome of forced evictions, broken lives and lost livelihoods; Conference: Social Science Research Seminar Series at the Batanai Campus, Midlands State University, Gweru, Zimbabwe - Madebwe, Crescentia; Togo, M.; Madebwe, Victor; Pazvakawambwa, L. (Midlands State University, 2016)
Using situational analysis, household questionnaires and interviews the paper analyzes socio-economic impacts of Operation Murambatsvina in two residential areas in Gweru. The number of households sharing a house ranged from one (66%), two (23%) and three (11%). Living rooms (23%), kitchens (28%) and dining rooms (63%) were used as sleeping quarters. Average monthly household income was Z$4 018 443 inclusive of salaries, rentals, remittances and income from informal activities. Households with backyard shacks (27%), illegal extensions to houses (9%), illegal fowl runs (47%), illegal business premises (8%) and illegal tuck shops (8%) had such structures demolished. Seventy-nine percent of the structures had been in use for over 5 years. Monthly household income loss due to demolitions averaged Z$2 227 400. Seventy-seven percent of respondents had not received formal prior notice about the demolitions and evictions. Thirty-five percent of evictees sought accommodation in the ‘main’ house, 36% moved to other residential areas whereas 5% and 24% went to rural areas or unknown destinations respectively. Operation Murambatsvina truncated children’s education, caused instant homelessness, loss of livelihoods and dislocation from jobs and neighborhoods.